Moral obligation or medical obstacle: is the patients’ rights charter fit for purpose in the prehospital emergency setting? - Hackland, Stuart George (My University, 2021)
Humans, by virtue of their humanity, possess an intrinsic dignity. This dignity deserves respect, and that respect manifests in the allocation of rights. In South Africa, these rights include the right of access to healthcare. The National Department of Health, in their mandate to promote, protect and fulfil this right of access to healthcare, published their National Patients’ Rights Charter (PRC) in 1999. It comprises approximately twenty five rights a patient may expect from the healthcare system. However, the PRC is unsuitable for application in the prehospital emergency environment, where the setting is uncontrolled, time-pressured, and occupied with providing life-saving care to the highest acuity patients, for whom the slightest delay may prove fatal. In this research report I apply the ethical theory of Prima Facie Duty to argue that, in life-threatening emergencies, the paramedic is morally justified in withholding certain patients’ rights in favour of providing life-saving treatment and transport. As an alternative to the PRC, I formulate the Patients’ Emergency Rights Charter (PERC) tailored to the dynamic circumstances of the prehospital emergency setting in South Africa
A research report submitted in fulfilment of the requirements for the degree Masters of Science in Medicine (Bioethics and Health Law) to the Faculty of Health Sciences, School of Bioethics, University of the Witwatersrand, Johannesburg, 2021